PENGARUH KEBIJAKAN DIVIDEN, LEVERAGE DAN EARNING VOLATILITY TERHADAP VOLATILITAS HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS LQ45 - Siti Laeli Wahyuni; Dwi Artati (JURNAL EKONOMI PERJUANGAN, 2023)
This research aims to find out the effect of Return on Assets (ROA), Earning Per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) on the return of stocks with inflation as moderation variables in manufacturing companies of metal sub-sectors and the like listed on the Indonesia Stock Exchange (IDX). The population used in this study is metal sub-sector manufacturing companies and the like listed on the Indonesia Stock Exchange (IDX) for the period 2016-2020 with a total of 17 companies. The sampling method in this study is a purposive sampling method with the acquisition of the number of samples as many as 15 companies so as to produce data amounting to 75. The analytical techniques used are classical assumption tests, multiple linear regression test, hypothesis tests, and residual tests with the SPSS 25 program. The results showed that Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) had no effect on stock returns, Earnings Per Share (EPS) negatively affected stock returns, and inflation could not moderate the relationship of Return on Assets (ROA), Earning Per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) to return on shares.